BS EN IEC 61347-2-10. Controlgear for electric light sources. Part 2-10. Particular requirements for electronic invertors and convertors for high-frequency operation of cold start tubular discharge lamps (neon tubes) (17th July 2020) - British Standards Institution,
No abstract available